Green Synthesis and Characterization of Vanadium Oxide Nanoparticles using Plant Extract - Mahdi, Saba H.; Abdul karem, Lekaa k.; Khalil, Ahmed M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This study employed the biosynthetic technique for creating vanadium nanoparticles (VNPs), which are affordable and user-friendly; VNPs was synthesized using vanadium sulfate (VOSO4.H2O) and a plant extract derived from Fumaria Strumii Opiz (E2) at a NaOH concentration of 0.1 M. This study aims to investigate the potential applications of utilizing an adsorbent for metal ions to achieve environmentally friendly production and assess its antibacterial activity and cytotoxicity. The reaction was conducted in an alkaline environment with a pH range of 8–12. The resulting product was subjected to various characterization techniques, including Fourier transform infrared spectroscopy, ultraviolet-visible spectroscopy, x-ray diffraction (XRD), transmission- and scanning- electron microscopy (TEM, SEM). The measurement of crystal size in NPs was conducted using Debye Scherer's equation in x-ray diffraction, resulting in a value of 16.06 nm. On the other hand, in the same direction, the size of VO2 NPs was determined through SEM and TEM. Also, this work investigates the antibacterial properties of VO2 nanoparticles against four bacterial strains, comprising two gram-positive-negative types and one fungus strain, to evaluate its antifungal efficacy. Notably, the application of newly produced VNPs has demonstrated a significant potential for anticancer activity in cell lines. The SW480 cell line was subjected to MTT assay at various concentrations. The results suggested a positive correlation between concentration and percentage of inhibition. By calculating the IC50 value, which was determined to be 60.3 mg/mL, it can be inferred that this NPs holds potential for targeted therapy in colon cancer treatment. Also, the present study investigates the antibacterial activity of VNPs synthesized using a biosynthetic approach. The cell line SW480 was utilized to evaluate the efficacy of the synthesized VNPs; XRD was employed to analyze the structural properties of the synthesized material.